Relationship between Market Competition and Green Supply Chain Management Practices in Manufacturing Industry - Alina Shamsuddin; Wan Nurul Karimah Wan Ahmad; Nur Zulaikha Ismail; Eta Wahab; Wong Chin Fei (International Journal of Supply Chain Management, 2020)
There is a growing market and institutional demands for companies to implement green practices to produce environment friendly products and services. Therefore, more companies are integrating the green practices into their operations, which have increased the market competition. In order to improve their competitiveness in the market, companies are forced to adapt to changing market requirements by implementing practices that could differentiate themselves, such as green supply chain management (GSCM). This study aims to understand the relationship between market competition and GSCM practices among manufacturing companies in Penang and Johor, Malaysia. Data gathered from a survey among the companies were analyzed using descriptive and correlation analysis. The results revealed that the level of market competition in the manufacturing companies’ business environment and the implementation of GSCM practices were relatively moderate. A Spearman’s correlation analysis show that market competition had a moderate positive relationship with all GSCM practices studied, namely green purchasing, product eco-design, cooperation with customers, reverse logistics and internal environmental management. The findings highlight the role of market competition in promoting environment friendly behavior in manufacturing industry. In addition, they also show that more should be done by the industry to improve the sustainability of their supply chain practices.